(untitled) (Research, Society and Development, 2024)
Leaf-cutting ant species with economic importance are those of the genera: Atta and Acromyrmex. Natural baits with spores of these entomopathogenic fungi can be used in the biological control of pest species. Therefore, the aims of this research, were: 1) inventory the species of leaf-cutting ants in three agroecosystems; 2) evaluate the attractiveness of the natural bait based on orange peel albedo impregnated with a bioinsecticide; 3) compare the amount of baits carried between the different concentrations of the bioinsecticide, and 4) evaluate the difference in the times spent for the first meeting of the bait and beginning of the loading in the direction of the nest by Atta laevigata, in relation to the concentrations of conidia of the bioinsecticide. Active searches were carried out in the anthills to collect adults (“soldiers”) and identify the species. The evaluations of the natural baits occurred in four adult nests of A. laevigata, being offered 2g of baits per repetition. The position of the treatments was changed at each repetition. We found four species: Atta sexdens, Atta laevigata, Acromyrmex rugosus and Acromyrmex balsani. There was a significant difference between the total amount of loaded and unloaded baits, indicating that leaf-cutter ants were attracted by the baits and ignored the presence of Beauveria bassiana conidia. The time for first contact and start of loading, did not differ significantly between treatments, nor between loaded amounts of different treatments. The bait containing the bioinsecticide is attractive to Atta laevigata workers, regardless of the concentration of conidia.